Experimental study of the accuracy of balancing an axial fan by adjusting the masses and by passive auto-balancers - Filimonikhina, Irina; Nevdakha, Yuriy; Olijnichenko, Lubov; Pukalov, Viktor; Chornohlazova, Hanna (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports determining and comparison of the quality of dynamic balancing of rotating parts in the assembly (impeller) by correction mass and applying passive auto-balancers using the axial fan VO 06-300-4 as an example. The impeller is balanced in two planes of correction – from the side of a fairing and from the side of an electric motor’s shank. It was established that prior to balancing the magnitudes of root-mean-square values (RMS) of vibration speed at the casing of the fan correspond with a margin to the balance quality grade: 1x vibration components (1x) ‒ G2.5; total – G6.3. The main source of vibrations is the dynamic residual imbalance of the impeller. The basic component of vibration speeds is the 1x one (at a frequency of 25 Hz), that is, it can be reduced by balancing. The non-1x vibration components occur at subharmonic frequencies, 25/2 and 25/3 Hz, and are smaller by the order of magnitude. When the impeller is balanced by correction mass, the initial imbalances from the side of a fairing and a shank are, respectively, 81.4 and 115.2 g∙mm, and the residual ones are 7.4 and 7.2 g∙mm. The magnitudes of RMS of vibration speed can be reduced at the fan’s casing to the magnitudes corresponding to the balance quality grade (with a margin): 1x – G0.4; total – G2.5. The main contribution to the residual vibrations is made by the non-1x vibration components occurring at subharmonic frequencies. At dynamic balancing of the impeller by two ball auto-balancers, in the presence of any imbalances (in two planes of correction) that can balance the auto-balancers, the RMS of vibration speed at the fan’s casing correspond to the balance quality grade: 1x – G1; total – G2.5. Ball auto-balancers react to imbalances constituting not less than 3 % of their balancing capacity. The residual imbalances are not stable, but are not larger from the side of a fairing and a shank than, respectively, 22.2 g∙mm and 21.6 g∙mm. Research results are applicable for low-pressure axial fans, specifically VO 06-300/VO-12-300; VOG/VO-15-320; VO 2,3-130/VO 46-130. They make it possible to decide on the expediency of balancing fans by passive auto-balancers